Attitudes towards and rationale for antipsychotic polypharmacy among psychiatrists in Nigeria: Characteristics associated with high reported antipsychotic polypharmacy. (February 2017) - James, B.O.; Omoaregba, J.O.; Raji, S.O.; Imishue, O.E.; Okonoda, K.M.; Nyamali, Y.I.; Famuyiwa, P.A.; Correll, C.U.
Abstract: Antipsychotic polypharmacy (APP) is commonplace despite lacking evidence of its effectiveness. We aimed to identify psychiatrists' rationale for and attitudes towards APP and to determine if attitudes influence antipsychotic polypharmacy prescription rates in a survey of a nationally representative sample of Nigerian psychiatrists (of which a majority were senior trainees: 74.2%). Prescriber characteristics, practices and attitudes were compared in 'high' (>30%) vs. 'low' (≤30%) antipsychotic polypharmacy prescribers and results were adjusted for multiple comparisons. Altogether, prescribers reported utilizing antipsychotic polypharmacy in 36.2% of their patients. Compared to 'low' antipsychotic polypharmacy prescribers, 'high' prescribers were significantly more likely using first-generation antipsychotics (FGA) combination, to have attempted a switch to monotherapy in less patients, or been successful in doing so. 'High' and 'low' antipsychotic polypharmacy prescribers were equally moderately concerned about the effects of antipsychotic polypharmacy and also did not differ regarding reasons not justifying antipsychotic polypharmacy. In a multivariable, backward elimination logistic regression model, 'low' antipsychotic polypharmacy was associated with having successfully switched patients to monotherapy, whereas the 'high' antipsychotic polypharmacy was associated with preferring FGA+FGA combinations and aiming for a reduction of non-antipsychotic medications. Antipsychotic polypharmacy is common among psychiatrists in Nigeria, with 'high' and 'low' antipsychotic polypharmacy prescribers sharing similar concerns/attitudes, but differing regarding their primary aim for antipsychotic polypharmacy and in their specific antipsychotic polypharmacy use characteristics. Highlights: Nigerian psychiatrists reported using antipsychotic polypharmacy (APP) in 36.2% of patients. 'High' (>30%) and 'lower' (≤30%) APP prescribers did not differ on concerns about or reasons for APP. 'Lower' APP use was associated with having successfully switched patients to monotherapy. 'High' APP use was associated with first-generation APP and trying to reduce non-antipsychotics.